Child Sexual Abuse and HIV-Related Substance Use and Sexual Risk Across the Life Course Among Males and Females. Issue 5 (4th July 2017) - Scheidell, Joy D.; Kumar, Pritika C.; Campion, Taylor; Quinn, Kelly; Beharie, Nisha; McGorray, Susan P.; Khan, Maria R.
ABSTRACT: Child sexual abuse is associated with substance use and sexual risk behaviors during adolescence and adulthood, but no known studies have documented associations across the life course in a nationally representative U.S. sample. We used the National Longitudinal Study of Adolescent to Adult Health to measure associations between child sexual abuse and substance use and sexual risk behaviors during adolescence, young adulthood, and adulthood among males and females (n = 11, 820). Approximately 10% of females and 7% of males reported child sexual abuse. Associations with substance use were strongest during adolescence and lessened over time. Increased odds of sexual risk among those with a history of child sexual abuse remained consistent through the life course. Significant gender differences existed for some associations (e.g., adulthood multiple partners: males adjusted odds ratio (AOR) = 1.73, 95%CI:1.18, 2.53; females AOR = 1.11, 95%CI:0.79, 1.56). Trauma-informed prevention interventions should address child sexual abuse among both males and females to prevent substance use and sexual risk behavior throughout the life course.